THE IMPACT OF SIMPANG LIMUN MARKET REVITALIZATION ON TRADERS INCOME : A REVIEW OF ISLAMIC ECONOMICS - Mawaddah, Lely (LPPM Universitas Trunojoyo Madura, 2025)
AbstractThis research aims to analyze the impact of the revitalization of Simpang Limun Market on traders' income from an Islamic economic perspective. Market revitalization is an effort to improve the quality of infrastructure and governance of traditional markets to make them more competitive and efficient. This research uses a qualitative method with a descriptive approach, where data is obtained through interviews with traders and analysis of related documents. The research results show that market revitalization has had various impacts on traders. Some merchants experienced an increase in income, especially those who were able to utilize digital technology in marketing, while others experienced a decrease in income due to changes in location and increased competition, both in the market and with online merchants. From an Islamic economic perspective, market revitalization should fulfill the principles of justice (Al-'Adl), desire (Al-Mashlahah), honesty and transparency (Ash-Shidq Al-Amanah), as well as striving for freedom (Hurriyyah Tijariyyah). However, in practice, the distribution of revitalization benefits has not been evenly distributed, so some traders have difficulty adapting to the new system.Keywords: Market Revitalization, Income, Local Economic Growth